Inventarisasi Jenis-Jenis Ikan Genus Pangasius Di Sungai Kampar Kiri Provinsi Riau - Hermirita, Silvia; Elvyra, Roza (Biospecies, 2020)
The available data and complete information regarding the species of fish from Pangasius in the waters of the Kampar Kiri River is still lack, therefore the research done about the inventory of the species on fish from Pangasius in the waters of Kampar Kiri River. This study aims the list fish from Pangasius in the waters of the Kampar Kiri River, Kampar regency, Riau Province. Fish samples were collected from local fishermen from December 2017 to December 2018. The fish samples were then identified at the Zoological Labolatory of the Biology Department, University of Riau. In this study, the result showed that the fishes from Pangasius found in the Kampar Kiri River consists patin getah (P. nasutus), patin putih (P. hypophthalmus), and patin keramba (P. pangasius).